Fouling-proof triple stream 3D flow focusing based reactor: Design and demonstration for iron oxide nanoparticle co-precipitation synthesis. (6th April 2022) - Gkogkos, Georgios; Besenhard, Maximilian O.; Storozhuk, Liudmyla; Thi Kim Thanh, Nguyen; Gavriilidis, Asterios
Highlights: A millifluidic chip device with two sequential 3D flow focusing junctions was designed based on CFD simulations and manufactured via micromilling. The effect of channel height ratios on 3D flow focusing patterns was studied via CFD simulations for a cross-shaped flow focusing junction. A separation stream introduced in the first junction enabled fouling free operation of the millifluidic flow focusing device during iron oxide nanoparticle synthesis. Abstract: The primary limitation of millifluidic reactors used for (nano)particle synthesis is fouling, which is inherent to small channel devices. This work presents an approach for fouling-free particle production by utilising a novel millifluidic device to achieve a wall-free environment, where the particles are formed. The design was based on computational fluid dynamics (CFD) simulations and produced a 3-layer co-axial flow in two sequential flow focusing junctions. The device enabled the introduction of a separating stream that prevented premature reaction to avoid fouling at the confluence point. The flow focusing device was used for an iron oxide nanoparticle co-precipitation synthesis using tetraethylammonium hydroxide (TEAOH). For this synthesis, it was used to initiate particle formation, and was followed by a millifluidic capillary coil. Fouling resistance at the capillary coil was increased by using excess TEAOH. At elevated temperature (60 °C) the produced nanoparticles were of superior quality compared to room temperature operation.